A delegação de competências como cumprimento do princípio da eficiência : sistemática do ordenamento jurídico brasileiro - Koch, Camila Herzog (2013)
The analysis of the State of Law and their respective principles, embodied in some of the paradigms of international constitutional density, such as the Rule of Law, Bill of Rights, Ètat Légal and Rechsstaat, and highlighted the method of constitutional interpretation and constitutional considering guaranteeism neoconstitutionalism, will be the subject of the first part of the study of the present work. The development of this dissertation also involves examining the Brazilian constitutional system, from a historical perspective, relating to federalism and public administration with emphasis also in the fundamental right to good government and the constitutional principle of efficiency.Established these assumptions, the study effectively with the approach of administrative decentralization through delegation, advocated by Decree-law n. 200, February 25, 1967, and thus established these premises, and through the harvest of the public administration, passed the examination of the case of autarchy Inmetro, its historical and legal context, and also will be the examination of identification of its panorama of activity and its decentralized management model. Noting the practical approach of the federal regulatory system constitutional, and the final analysis will include an assessment of the delegation of powers and compatibility with the administration, according to the fundamental right to good administration pegged the greatest contribution to the constitutional principle of observance efficiency in public governance